Physiological aspect of Upavasa (langhana) w.s.r indigestion (Mandagni/Agnimandhya) - Saini, Mukesh; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda, the science of life, has much to discuss diet and fasting. Fasting is going without food and drink for a while. In Dharmashastra the langhana has been told as vrat which are often practiced by religious-minded people on certain specific religious days of the month. The verbal meaning of Agni is fire( digestive fire) and mandhya is decreased or reduced. According to Ayurveda, low or disturbed digestive fire is considered as the root cause of all the diseases. Agni mandhya is a chronic disease in which the digestion of food and nourishment of body tissue does not take place properly due to reduction in the digestive capacity of Agni. The process by which food is broken down into simple chemical compounds that can be absorbed and used as nutrients or eliminated by the body is called digestion.